EVALUATION OF THE MODEL OF ORGANIZATION OF THE EMERGENCY UNIT OF THE UNIVERSITY HOSPITAL, FACULTY OF MEDICINE OF RIBEIRÃO PRETO, UNIVERSITY OF SÃO PAULO, BASED ON THE ADOPTION OF THE NATIONAL POLICY OF EMERGENCY CARE AND HUMANIZATION AS A REFERENCE - Santos, José Sebastião; Scarpelini, Sandro; Brasileiro, Sérgio Luís L.; Ferraz, Clarice Aparecida; Dallora, Maria Eulália L. V.; Sá, Marcos Felipe Silva (Medicina (Ribeirao Preto), 2003)
Innovative experiences directed specifically at complete care and training and professional habilitation in the urgency area are recent in Brazil and are being influenced by the French-German and Anglo-American models. The incorporation of the Mobile Emergency System (Sistema de Atendimento Móvel de Urgência, SAMU) and of Medical Regulation into the assistance network started after the 1995 French-Brazilian collaboration. In Brazil, SAMU was set up in 1996 and the Medical Regulation of the entire urgency demand was set up in 2000. In Brazil, the immediate emergency care is multidisciplinary, as is the case for the French-German model, but the systematic regulation of knowledge and of assistance practices of the health teams for advanced life support has been influenced by Anglo-American programs such as Advanced Cardiac Life Support, Advanced Trauma Life Support, Pediatric Advanced Life Support, and Basic Life Support, among others.These strategies adapted to Brazilian reality have contributed to the transformation of the old model of organization of emergency care and have led to revision of the curricular content and of academic organization. The problems of urgency care in large urban centers and some successful experiences within the Unified Health System (Sistema Único de Saúde, SUS) have helped the formulation of National Policies of Urgency Care , and of Humanization (PNH) of the Health Ministry. It is the task of the Ministry of Education, of Training Centers, of Class Councils and of Agencies for the Support of Research, in syntony with SUS, to formulate standards for training, for the exercise of the profession and for investigation in urgency care.Over the last few years, the Emergency Unit of the University Hospital, Faculty of Medicine of Ribeirão Preto, University of São Paulo (UE-HC), by applying the concepts contemplated by the Urgency Care Regulation and by SAMU, has participated in the configuration of a regional network for emergency care that has been arranged in hierarchical order, regulated and humanized. The clinical services of UE-HC linked to the Departments of Application of FMRP-USP and supported by the Center of Emergency Studies have helped redefine the assistential and educational mission of this Unit. Overcrowding was solved by a significant reduction in the number of consultation and in the rate of occupation and, as expected, there was an increase in mean time of permanence, in the complexity of the cases attended and in the mean costs of hospitalization. Thus, the Emergency Unit has been transformed into a reference center for care of high complexity and for the training and professional habilitation of the professionals who deal with emergencies. On this scenario, possibilities are rising for a critical reflection about practices already instituted, about the preparation for the production of new knowledge and about the bases for the creation of an academic department and of the specialty of medical emergencies.